Development Of Flipcharts As A Learning Media With Material On The Human Digestive System For Students At SMP Negeri 4 Bitung - Yonggi Arvindo Tantu; Maurits H. Sumampouw; Mercy M. F. Rampengan (Institut Nalanda, 2023)
This research was carried out by looking at adapting a product to be developed to existing problems in the learning process, especially for learning media, which may have little impact on students. The development of flipcharts as a learning medium could be an effort that has a good impact on the continuity of learning activities. This research model uses research and development using stages 4 – D. The process of developing flipchart media is carried out until the dissemination stage. This model includes Devine (analysis), Design (Design), Develop (Development), and Dissemination. The Devine stage includes initial observations at the school where the research was conducted, namely at SMP Negeri 4 Bitung. This is then continued with the product design stage, including preparing materials and creating images arranged to convey ideas about the media that will be developed. In the next stage, product development is carried out, which includes assessments from material experts and media experts as well as with study field teachers to see whether a product is suitable for application in learning. The next stage is Dissemination, which includes trials on students, and this stage is carried out in small group trials of 5 to 20 students at SMP Negeri 4 Bitung. The results of the research carried out show that from the validation test, material experts got an average score of 80%, media experts got an average score of 80%, subject teachers got an average score of 84%, and from trials on Students obtained an increase in their test scores before the flipchart media was 65%, after the flipchart media the students' scores increased to 89%. So, it can be concluded that flipcharts as a learning medium are suitable for use and are adequate for application in learning.